Association of brain amyloid accumulation and glucose hypometabolism with memory loss: Neuroimaging / Multi‐modal comparisons. (7th December 2020) - Wang, Ying; Huang, Qi; Ren, Shuhua; Huang, Lin; Jiang, Donglang; Li, Junpeng; Guan, Yihui; Guo, Qihao; Xie, Fang
Abstract: Background: Memory loss is the main syndrome of Alzheimer's disease (AD). Extracellular accumulation of amyloid‐β (Aβ) neuritic plaques and neurodegeneration such as glucose hypometabolismwere the main pathology of AD. In this study, we try to figure out the association of Aβ accumulation and glucose hypometabolism with memory loss. Methods: 91 normal cognition (NC) healthy volunteers, 37 subjective cognitive decline (SCD), 32 mild cognition impairment (MCI) and 34 AD patients were enrolled in this study from Chinese preclinical Alzheimer's disease (C‐PAS), which is initiated by Shanghai Jiao Tong University Affiliated Sixth People's Hospital and Huashan Hospital. 6 types of neuropsychological tests from 3 cognitive core, including Auditory verbal learning test (AVLT) 30‐minute delayed free recall and AVLT recognition for memory, MMSE, Moca B were performed. FDG and amyloid PET (18F‐Flortabetapir) were conducted in these participants. 18F‐FDG and 18F‐Flortabetapir PET images were coregistered to the individual structural MRI images and then spatially normalized into MNI space. The associations of FDG and Aβ with impairment of language were explored by performing multiple regression between the 18F‐FDG and neuropsychological scores, as well as 18F‐Flortabetapir PET images and neuropsychological scores with age, gender, educationalyears as covariates. The statistical level was set at p<0.05 with FDR correction and a minimum cluster extent Ke>20 voxels. Results: No relationship was found between memory loss and amyloid accumulation. Glucose metabolism in precuneus, middle frontal cortex, cuneus, posterior cingulate gyrus has association with AVLT 30‐minute delayed free recall. Association was observed between glucose metabolism in inferior frontal cortex, insula and AVLT recognition. Conclusion: Associations were observed between memory loss and glucose hypometabolism, but no association was found between amyloid and memory loss.